The Role of Local Officials in New Democracies: Evidence from Indonesia - Martinez-Bravo, Monica (American Economic Review, 2014)
This paper shows that the body of appointed officials that a new democracy inherits from the previous regime is a key determinant of the extent of electoral fraud and clientelistic spending in new democracies. I develop a model that predicts that appointed officials have stronger incentives to influence voters during national level elections because of their career concerns. I test the implications of the model using data from Indonesia's transition to democracy. Both the pattern of alignment of electoral results between village and district levels and the pattern of subsequent turnover of appointed village heads corroborate the predictions of the model. ( JEL D72, H77, H83, O17, O18)